Language for teaching purposes : an analysis of the spoken language needs of non-native speaker language teachers - Riordan, Emma (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2014)
It is understood that the non-native speaker language teacher (NNSLT) requires a high level of language proficiency to be an effective and confident professional. However, the teaching of language to NNSLTs is often neglected in teacher training programmes (Medgyes, 1999), and it is not clear what the required language proficiency of this group entails (Braine, 2010). This thesis proposes that non-native speaker language teachers would benefit from language training designed specifically for them and adopts a Language for Special Purposes approach to assess their language needs. The language needs analysis focuses on non-native speaker teachers of German at second level schools in Ireland using a mixed methods research approach. Firstly, a document analysis and semi-structured interview investigated language teaching experts' and policy makers' expectations of language teachers' language skills. Secondly, a questionnaire regarding teacher language use was sent to all schools in Ireland where German is taught to gather the teachers' views on their own language needs. Lastly, 19 German classes given by six different teachers were observed, recorded, transcribed and analysed yielding nearly 63,000 words of spoken classroom discourse.
Keywords: Linguistics, Speech & Communication Sciences, Ph.D.; Ph.D. Trinity College Dublin